Basic Principles in Quality PAI Learning Assessment - Ema Sulastri (Bansigom Na Publisher, 2025)
Assessment in Islamic Religious Education (PAI) learning is a crucial aspect of the educational process aimed at measuring and enhancing the quality of learning. This article discusses the fundamental principles of quality assessment in PAI learning, basedon various literature and recent studies. In this context, assessment is not solely focused on final outcomes but also on the learning process itself. This research employs a literature review method by identifying and selecting articles, journals, and books focusing on evaluation and assessment in Islamic education. The findings reveal that the fundamental principles of PAI learning assessment should include:1) Validity, meaning that the assessment must accurately measure what it is intended to measure;2) Reliability, which pertains to the consistency of assessment results;3) Objectivity, ensuring that the assessment is free from the educator's personal bias;4) Connectivity, referring to the alignment of assessment with students' learning experiences and their social contexts; and5) Feedback, which helps students understand their strengths, weaknesses, and areas for improvement.This study aims to provide educators with deeper insights into implementing effective and relevant assessments in PAI learning